2019
DOI: 10.2147/ijn.s230376
|View full text |Cite
|
Sign up to set email alerts
|

<p>Co-Delivery of Docetaxel and Salinomycin to Target Both Breast Cancer Cells and Stem Cells by PLGA/TPGS Nanoparticles</p>

Abstract: Conventional chemotherapy is hampered by the presence of breast cancer stem cells (BCSCs). It is crucial to eradicating both the bulky breast cancer cells and BCSCs, using a combination of conventional chemotherapy and anti-CSCs drugs. However, the synergistic ratio of drug combinations cannot be easily maintained in vivo. In our previous studies, we demonstrated that the simultaneous delivery of two drugs via nanoliposomes could maintain the synergistic drug ratio for 12 h in vivo. However, nanoliposomes have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 50 publications
0
43
0
1
Order By: Relevance
“…In this study, we designed to link the hydroxyl group of DAS and the carboxyl group of HA through ester construction to obtain an amphiphilic complex with DAS as the hydrophobic segment and HA as the hydrophilic segment. HA acts as a ligand for CD44 protein, which can target tumor cells overexpressing CD44 receptor, thus enabling targeted drug delivery (Gao et al., 2019 ). At the same time, the addition of TPGS to the carrier increases the stability of the nanoparticles, inhibits the P-gp activity, and increases the intracellular accumulation of the drug.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we designed to link the hydroxyl group of DAS and the carboxyl group of HA through ester construction to obtain an amphiphilic complex with DAS as the hydrophobic segment and HA as the hydrophilic segment. HA acts as a ligand for CD44 protein, which can target tumor cells overexpressing CD44 receptor, thus enabling targeted drug delivery (Gao et al., 2019 ). At the same time, the addition of TPGS to the carrier increases the stability of the nanoparticles, inhibits the P-gp activity, and increases the intracellular accumulation of the drug.…”
Section: Introductionmentioning
confidence: 99%
“…Shafiei-Iranneja et al [ 146 ] demonstrated that the use of polymeric NPs is a good strategy to combat MDR in doxorubicin-resistant breast cancer (MCF-7/DOX) cells. However, the nanoencapsulation of these NPs together with D-α-tocopheryl polyethylene glycol 1000 succinate (TPGS), a compound used for surface modification of PLGA NPs, has shown a higher cytotoxicity and apoptosis in breast cancer cells [ 147 ]. In addition, a higher intracellular drug accumulation and a reduced drug efflux, associated with a decreasing cellular ATP content and an inhibition of P -gp activity, have been observed [ 146 ].…”
Section: Polymeric Nanoparticles In Oncologic Treatmentmentioning
confidence: 99%
“…9 What is more, another attractive characteristic of PLGA over other nanoparticles is that PLGA is one of the best characterized biodegradable copolymers because it decomposes into nontoxic lactic acid and glycolic acid and further into H 2 O and CO 2 eliminated from the body with low to no toxicity. 10,11 According to all these advantages of PLGA NPs, are extensively used in a variety of fields, for example, PLGA NPs loaded with corresponding therapeutic drugs can cross the blood-brain barrier and reach the central nervous system. 12 In addition to the intrinsic properties of PLGA NPs, incorporating targeting ligands, such as small molecules, peptides, antibodies, and aptamers onto their surface make them better with respect to targeting strategy, biocompatibility, and preferential accumulation.…”
Section: Plga-based Nanoparticlesmentioning
confidence: 99%
“…15 In comparison to monotherapy, anticancer drugs encapsulated in PLGA nanoparticles show good biocompatibility, strong cytotoxicity, significant antitumor activity and minimal systemic toxicity. 11,15 Co-encapsulation of two drugs to the tumor via single nanoparticles could better maintain the synergistic drug effect in vivo than the coadministration of two single drugs and drug-carried nanoparticles. 16 What is more, as a kind of biodegradable organic polymer, PLGA has good modifiability.…”
Section: Plga-based Nanoparticlesmentioning
confidence: 99%